Cloud-Based Service Oriented Architecture for Managing The Friday Charity Program to Support Social Care Character Education in Primary Schools - Firdaus Muttaqin; Khairiah Khairiah (Journal of Primary Education (JPE), 2026)
Manual recording, delayed recapitulation, data redundancy, and limited access to information are still issues in managing donation data for the Friday Charity Program in elementary schools. By using a Service Oriented Architecture (SOA) approach based on cloud computing, this research aims to develop and evaluate the Infaq Data Management System for the Jumat Sedekah Program. The research uses an evaluative system development design. Observation, interviews, and program document examination were used to conduct a needs analysis. This system is built using Unified Modelling Language (UML), using PHP and MySQL, and using web services as a mechanism to integrate data between the central system and units. White box testing, black box testing, and user acceptance testing are the methods used to evaluate the system. Based on 26 complete responses evaluated, the system received an average score of 4.09 for display features, 4.05 for ease of use, and 4.03 for performance. All three aspects meet the standards. The results of the functional testing also show that the main tasks of the system, such as user management, collection of donations, beneficiaries, provision of assistance, and data exchange through web services, can be carried out according to the design. The results show that the cloud computing-based SOA can help manage the Friday Charity Program in a more structured and integrated manner. However, this research does not directly measure changes in students' social care character. Therefore, the system's contribution to character education is considered to assist in the implementation and supervision of the school's social programs.Keywords: Service Oriented Architecture; cloud computing; infaq management; Friday charity program; primary education; social care character